Metabolic characteristics of programmed cell death‐ligand 1‐expressing lung cancer on 18F‐fluorodeoxyglucose positron emission tomography/computed tomography. (4th October 2017) - Takada, Kazuki; Toyokawa, Gouji; Okamoto, Tatsuro; Baba, Shingo; Kozuma, Yuka; Matsubara, Taichi; Haratake, Naoki; Akamine, Takaki; Takamori, Shinkichi; Katsura, Masakazu; Shoji, Fumihiro; Honda, Hiroshi; et al.
Abstract: Programmed cell death‐1 (PD‐1) and programmed cell death‐ligand 1 (PD‐L1) have been identified as novel targets of immunotherapy of lung cancer. In present study, we evaluated the metabolic characteristics of lung cancer by using 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F‐FDG PET/CT) with regard to PD‐L1 protein expression. PD‐L1 protein expression was evaluated by immunohistochemistry with the antibody clone SP142 in 579 surgically resected primary lung cancer patients. Cases with less than 5% tumor membrane staining were considered negative. We examined the association between the frequency of PD‐L1 protein expression and the maximum standardized uptake value (SUVmax) in preoperative 18 F‐FDG PET/CT. The cut‐off values for SUVmax were determined by receiver operating characteristic curve analyses. The SUVmax was significantly higher in nonsmall cell lung cancer (NSCLC) patients with PD‐L1 protein expression compared with those without PD‐L1 protein expression ( P < 0.0001). However, there was no correlation between SUVmax and PD‐L1 protein expression in patients with neuroendocrine tumors ( P = 0.6545). Multivariate analysis revealed that smoking, the presence of pleural invasion, and high SUVmax were independent predictors of PD‐L1 positivity. PD‐L1‐expressing NSCLC had a high glucose metabolism. The SUVmax in preoperative 18 F‐FDG PET/CT was a predictor of PD‐L1 protein expression in patients with NSCLC. Abstract : PD‐L1‐expressing NSCLC had a high glucose metabolism. The SUVmax in preoperative 18F‐FDG PET/CT was a predictor of PD‐L1 protein expression in patients with NSCLC.